2020
DOI: 10.1039/d0ta04765a
|View full text |Cite
|
Sign up to set email alerts
|

Energetic decomposition yields efficient bimetallic Cu MOF-derived catalysts

Abstract: Metal-organic frameworks (MOFs) have recently emerged as efficient self-sacrificial templates to fabricate porous carbon-supported metal nanoparticles (NPs). Due to synergistic effects, the catalysts containing bimetallic NPs represent an active frontier...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Therefore, with the doping of Ni, Zn has a smaller particle size. 39 Unfortunately, there is no visible peak corresponding to the Ni phase, which may be due to the low doping level of Ni or the high dispersion of Ni.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with the doping of Ni, Zn has a smaller particle size. 39 Unfortunately, there is no visible peak corresponding to the Ni phase, which may be due to the low doping level of Ni or the high dispersion of Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Wang and Sorenson et al also found that the size of bimetallic MOF decreased with the addition of secondary metals. [47][48][49] H 2 adsorption performance Fig. 5 show the H 2 adsorption isotherms of ZIF-8, NZ-X at 77 K and 1 bar.…”
Section: Structure Characterizationmentioning
confidence: 99%
“…Finding a proper photocatalyst that is active in visible light is of researcher’s interest. Among various photocatalytic porous materials, metal–organic frameworks (MOFs) are extensively investigated due to their large surface area, , tunable structure, low density, , high crystallinity, , and tunable pore size distribution. , …”
Section: Introductionmentioning
confidence: 99%